Scaling Smallholder Farmer Empowerment: Lessons from the Lifelong Learning Program in Uganda - Kalibwani, Rebecca; Kakuru, Medard; Carr, Alexis; Tenywa, Moses (Journal of Learning for Development, 2021)
An evaluation study of the Lifelong Learning for Farmers (L3F) program was undertaken in two sites; in the central and northern regions of Uganda. Propensity Score Matching (PSM) was used to measure the impact of the program on crop and household income, as well as the empowerment levels of its participants. The two sites had differences not only in geographical location but in historical background and implementation of the program, which may have influenced the livelihood outcomes. Despite these differences, the results of the study confirm the potential of the L3F approach to raisen participants’ crop and household income relative to non-L3F counterparts, significantly so for women participants. There is also sufficient evidence to confirm that L3F positively contributes to farmer empowerment, and, subsequently, their livelihood. The paper draws lessons for scaling the empowerment process using the lifelong learning for farmers’ model in Uganda.
Keywords: Propensity Score Matching; Empowerment; Lifelong learning for farmers